Leveraging SWOT and Business Model Canvas to Improve Operational Efficiency through Digital Transformation - Azmi Muhammad Islam; Khusnul Khotimah (Journal of Innovation, Business Management and Entrepreneurship, 2025)
Digitalization in the banking sector has become a critical driver of operational efficiency and improved service quality. This study aims to evaluate the role of digital transformation in enhancing operational efficiency at Bank Syariah Indonesia (BSI), Yogyakarta Kaliurang Branch, with a specific focus on the implementation of the Byond application as a replacement for BSI Mobile. The adoption of Byond has significantly accelerated transaction processes, enhanced customer experience, and reduced administrative workloads for bank staff. Moreover, digitalization supports human resource optimization by enabling more automated and error-minimized workflows. The findings reveal that while digital initiatives have produced substantial positive impacts, challenges remain, particularly in customer adoption of new technologies. These challenges necessitate more intensive outreach and educational strategies. Therefore, although digitalization has markedly contributed to operational efficiency at BSI, sustainable development strategies are still required to ensure that its benefits are fully realized by all stakeholders.